COO effect: business opportunities for Middle Eastern entrepreneurs - Supramaniam, Sivakumari *; Gaur, Sanjaya S. *; Izian Idris, *; Cheng, Boon Liat * (2018)
The purpose of this paper is to identify the potential business opportunities for Middle Eastern entrepreneurs by understanding the Malaysian Muslim’s ways of experiencing and realising value of products originating from Middle Eastern countries.Phenomenography approach has been used to identify the variations among the Muslim consumers’ ways of experiencing Middle Eastern products.The authors reported that Muslim consumers considered the country of origin as an important cue that affects their knowing, understanding, judging and acting on products originating from Middle Eastern countries.Understanding developed from the Malaysian Muslim consumers enabled authors to suggest business opportunities for Middle Eastern entrepreneurs to enter and expand their operations in other leading Islamic countries